AN ENGLISH AS A LINGUA FRANCA (ELF) PERSPECTIVE IN ASIAN ENGLISH LANGUAGE TEACHING (ELT) - Salam Mairi (Universitas Negeri Padang, 2016)
The global spread of English as a Lingua Franca (ELF) has implications for practice in English Language Teaching (ELT) classrooms. This paper presents a study on attitudes toward ELF in ELT which is crucial to its incorporation because attitudes are proven to influence the learning output in ELT. It uses a mixed method approach through questionnaire on attitudes toward ELF which contains a modified Verbal Guise Technique (VGT) complemented with semi structured interview. 70 university students and 4 lecturers from three English departments in Japan (Waseda University and Sophia University) and Indonesia (Universitas Negeri Jakarta) were involved in filling out the questionnaire and semi structured interview sessions. The results highlight positive attitudes towards ELF and its incorporation into ELT (Japan: 3.71 and Indonesia: 3.51). In addition, factors which influence these attitudes (aspects related to language learning experience) were proven significant. It also suggests ways to incorporate an ELF perspective into the ELT classrooms which were discovered through interview sessions. Further, it addresses the issue in the gap between theory and practice in research on Global Englishes in Language Teaching (GELT) where ‘conceptual gap’ is often found. The study is of interest of those interested in ELT curriculum evaluation and design to meet the needs of both ELT and ELF community in countries like Japan and Indonesia.